VIRTUAL LEARNING OF ELECTRONICS - Ptak, Paweł (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2022)
The development of computer technology has enabled the emergence of new teaching opportunities in an artificial, virtual environment. It is then possible to work with electronic systems without the possibility of physical access to them and without measuring equipment. Such teaching and work with electronic systems was possible in a laboratory with computer stations with appropriate software. Only the development of network technology, and in particular the Internet, made it possible to fully virtual work at a distance. Until now, virtual learning has only been an alternative to teaching in a real hardware lab. It was also a supplement to the work that was carried out in the course of practical teaching with students. It was only the emergence of the Covid-19 epidemic that made this type of remote work learning a necessity, but also the only alternative in the event of school closings and quarantines. The necessity of distance learning inspired the use and development of many programs and information systems for this purpose. The paper presents selected programs that can be used and are used to learn electronics at a distance while working remotely. Each of these systems has its own advantages and disadvantages and can meet specific requirements.